Simple sediment model : a tool to estimate nutrient regeneration in Baltic Sea sediments - Andrejev, Oleg; Savchuk, Oleg; Perttilä, Matti (Merentutkimuslaitos, 2015)
Sisältää myös kaksi muuta artikkelia: Matti Mälkki: Distribution of sediments and suspended matter in the Gulf of Finland - the Central Baltic Proper transect with a particular emphasis of transportation: minerogenic evidence Stanislav Denisenko: Long-term changes of zoobenthos biomass in the Barents Sea